População com HIV e AIDS : traços da realidade socioepidemiológica em Aracaju/SE - Souza, Cleverton Alves de (2022)
The Acquired Immunodeficiency Syndrome (AIDS), an infection caused by the Human Immunodeficiency Virus (HIV), as far as a complex global public health issue, is marked by transformations, prejudices, contradictions, and social tensions in its confrontation. In times of capital offense, strategies are adopted to benefit macroeconomic policy, with implications in the law sphere and social policies. In Brazil, this scenario has shaped health policy trends that are at odds with constitutional principles and guidelines, reflecting on responses Against the virus through inclinations that focus resources on biomedical interventions, withdraw investments in preventive actions, and demobilize activities developed by civil society. Therefore, this work investigated the population living with HIV and AIDS in Aracaju, Sergipe, from 2016 to 2020. The general outcome of this work was to analyze the occurrence of HIV infection and AIDS diagnoses in the city of Aracaju, based on data from the Sergipe State Health Department (SSHD). As specific outcomes, the following were taken: 1) characterize the sociodemographic aspects (education, sex at birth, age group, and race/color) of the people with HIV and of individuals diagnosed with AIDS; 2) Investigate the transmission means; 3) Identify the cases of pregnant women with HIV and AIDS; 4) Check HIV and AIDS records by year of diagnosis and death cases. By revealing the reality of this population segment, this research brought to the debate important elements that make it possible to reflect on these changes at national and local levels, always in articulation with context-reality-subject. Regarding the methodological aspects, it was an exploratory study with a qualitative/quantitative approach, based on the historical-dialectical materialista method, as well as bibliographic and documentary research. The occurrence of 1073 cases of HIV was found in the city of Aracaju, displaying the predominance of the following indicators: 76.0% are men; 58.1% are aged from 20 to 34; 79.2% are black; 30.5% have finished High School; 43.9% are heterosexuals (0.3% out of that use injectable drugs); 97.5% residents in the urban area; 4.7% are pregnant, and the percentage of deaths was 1.3%. There were a total of 691 cases of AIDS, and the following indicators prevailed: 78.1% are men; 42.4% are aged from 20 to 34 years old; 85.0% are black; 25.0% finished High School;51.8% are heterosexual (1.0% ou of that use injectable drugs); 97.6% live in urban areas; 1.0% are pregnant and there were 12.9% cases of deaths. This environment, although demonstrating singularities, reflects the epidemic situation at a national level, which reason the need to understand these individuals in the web of multiple imbricated determinations in the susceptibility to the virus and the pathology development. It is related, amongst Other factors, to the unequal relations of social class, gender and race/ethnicity, and disproportionality in income concentration as well. Furthermore, it also signals the importance of guaranteeing access to the right and health care in an equitable and intersectoral manner.